2022
DOI: 10.1021/acs.orglett.2c00242
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Monooxygenase for Catalyzing C-42 Hydroxylation of the Glycine-Derived Fragment in Hangtaimycin Biosynthesis

Abstract: A hybrid trans-AT PKS/NRPS gene cluster htm was identified with defined boundaries for hangtaimycin biosynthesis in Streptomyces spectabilis CPCC200148. Deoxyhangtaimycin, a new derivative of hangtaimycin, was identified from the htm11 gene knockout mutant. In vitro biochemical assays demonstrated that the cytochrome P450 monooxygenase Htm11 was responsible for the stereoselective hydroxylation of deoxyhangtaimycin to hangtaimycin. More importantly, deoxyhangtaimycin showed activity against influenza A virus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…As has been demonstrated, a cytochrome P450 monooxygenase in HTM biosynthesis is responsible for the C-42 oxidation of deoxyhangtaimycin to HTM [ 14 ]. The installed hemiaminal functionality is unstable and easily lead to the degradation of HTM into HTM 222 and a larger lactone-polyene peptide fragment [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been demonstrated, a cytochrome P450 monooxygenase in HTM biosynthesis is responsible for the C-42 oxidation of deoxyhangtaimycin to HTM [ 14 ]. The installed hemiaminal functionality is unstable and easily lead to the degradation of HTM into HTM 222 and a larger lactone-polyene peptide fragment [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accompany with the unique structure of HTM, it presents good hepatoprotective bioactivities [ 13 ]. Previous work showed that, during its biosynthesis, there existed dehydrating bimodules to install a double bond in HtmA1 [ 12 ] and a P450 enzyme to add a hydroxyl group at C-42 [ 14 ], but the exact methylation in its biosynthetic pathway is still unknown. In this study we report the characterization of the three methylases in HTM biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthetic machinery is composed of a hybrid trans-acyltransferase (trans-AT, [3,4]) polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS) [2] with a dehydrating bimodule [5,6] involved in the installation of the remaining Z-configured double bond within the polyketide backbone [7]. Furthermore, a cytochrome P450 monooxygenase was recently shown to be responsible for the oxidation of deoxyhangtaimycin (3), a compound with antiviral activity, to 1 [8]. The thereby installed Scheme 1: Structures of hangtaimycin (1) and its co-metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid trans -AT PKS-nonribosomal peptide synthase (NRPS) gene cluster has been shown to produce the secondary metabolite hangtaimycin 31 in Streptomyces spectabilis CPCC 200148. 24 Knockout mutant and in vitro biochemical experiments identified Htm11 as a cytochrome P450 monooxygenase that performs a stereoselective C-42 hydroxylation to give hangtaimycin.…”
mentioning
confidence: 99%